2022
DOI: 10.1155/2022/9112587
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Classification of Prostate Cancer Identification and Classification Based on Improved Convolution Neural Network

Abstract: Prostate cancer is one of the most common cancers in men worldwide, second only to lung cancer. The most common method used in diagnosing prostate cancer is the microscopic observation of stained biopsies by a pathologist and the Gleason score of the tissue microarray images. However, scoring prostate cancer tissue microarrays by pathologists using Gleason mode under many tissue microarray images is time-consuming, susceptible to subjective factors between different observers, and has low reproducibility. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The Gleason score (GS), a predictive index for disease progression, derives from a pathologist's evaluation of prostate cancer tissue microarrays. Basically, five different prognostic groups were classified according to the final score, when ≤6 points usually mean better prognostic results [ 15 ]. The abundance of M2-like macrophages is also strongly associated with a higher GS and indicates worse specific survival and recurrence-free survival after hormone therapy [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Gleason score (GS), a predictive index for disease progression, derives from a pathologist's evaluation of prostate cancer tissue microarrays. Basically, five different prognostic groups were classified according to the final score, when ≤6 points usually mean better prognostic results [ 15 ]. The abundance of M2-like macrophages is also strongly associated with a higher GS and indicates worse specific survival and recurrence-free survival after hormone therapy [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%